Developing a framework for managing the night-time economy in Wales: a Health Impact Assessment approach. Issue 1 (2nd January 2018) - Ashton, Kathryn; Roderick, Janine; Parry Williams, Lee; Green, Liz
Abstract: The night-time economy can have major impacts on the health and well-being of individuals. A framework for managing a safe and prosperous night-time economy aids the coordinated approach to develop sustainable, healthy and safe night-time economies. This case study outlines the approach of a prospective Health Impact Assessment (HIA) to re-develop an existing reactive framework for managing the night-time economy in Wales. Inclusion of a range of stakeholders in the process enabled the reformulation of realistic proactive objectives which account for both health and well-being. This article highlights the benefits of HIA and can be used to inform future policy developments.